The Correlation Among Reading Habits, Reading Motivation, and Reading Comprehension of The Eleventh Grade Students of SMA Negeri 10 Palembang - Aditya, Andi; Dafa, Fadhilah; Budiyanto , Darmawan; Ridho , M Rasyid (Journal of English Education, 2023)
The effect of comprehension is determined not only by whether or not the text makes sense but also by the information it contains. The purpose of this research was to determine whether or not there was a correlation among class XI students' reading habits, reading motivation, and reading comprehension at SMA Negeri 10 Palembang. 130 students from classes XI MIA 5, XI MIA 6, and XI MIA 7 were chosen using the purposive sampling technique. The correlational method applies to this study. Questionnaires and tests have been data collection instruments. To analyze the data, the writer used Kolmogorov-Smirnov normality testing, SEM-PLS for correlation analysis, with SmartPLS version 3.2.9. The latent variable correlation results for the significance of reading habits and reading comprehension in students show the correlation value (0,989) was higher than r-table (0,172). This means that the significant value of correlation was included in the very high category, and the results of the latent variable correlation on the significance of students' reading motivation and reading comprehension show that the correlation value (1,000) was higher than the r-table (0,172). This means that the significant value of correlation was included in the very high category. The correlation coefficient was found to be significant. It also implies there was a statistically significant correlation among their reading habits, reading motivation, and reading comprehension. The null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted, as determined by the writer. In conclusion, this result is explained by the fact that there was a significant relationship among reading habits, reading motivation, and reading comprehension.